Peran Fear of Failure sebagai Mediator antara Regulasi Emosi dan Prokrastinasi Akademik pada Mahasiswa Semester Akhir - Dila Estiyana; Dyan Evita Santi; Inka Sukma Melati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Academic procrastination is one of the most common problems experienced by final-year undergraduate students during the completion of their final thesis. This condition is influenced by various psychological factors, including emotion regulation and fear of failure. This study aimed to examine the mediating role of fear of failure in the relationship between emotion regulation and academic procrastination among final-year undergraduate students. This study employed a quantitative approach with a correlational design involving a mediation model. The participants consisted of 141 final-year undergraduate students from various universities in Surabaya who were selected using a quota sampling technique. Data were collected using the Emotion Regulation Scale, the Fear of Failure Scale, and the Academic Procrastination Scale, and were analyzed using path analysis with the JASP statistical software. The results indicated that emotion regulation had a significant negative effect on academic procrastination (β = -0.535; p < .001) and a significant negative effect on fear of failure (β = -0.504; p < .001). In contrast, fear of failure did not have a significant effect on academic procrastination (β = 0.011; p = .893), indicating that it did not mediate the relationship between emotion regulation and academic procrastination (indirect effect = -0.006; p = .893). Based on the findings it can be concluded that emotion regulation reducing academic procrastination among final-year undergraduate students, however fear of failure did not function as a mediating variable in this relationship. These findings indicate that emotion regulation contributes more substantially to explaining academic procrastination than fear of failure. Therefore, enhancing emotion regulation may serve as one of the primaries focuses on efforts to reduce academic procrastination among final-year undergraduate students.